ANALISIS KETERBUKAAN INFORMASI PUBLIK DALAM PERSPEKTIF HAM DI KOTA SAMARINDA - Prasetyo, Bayu (LPPM, Universitas Muhammadiyah Riau, 2024)
Public information transparency is a fundamental right that supports the principles of Human Rights by strengthening government transparency and accountability. This study aims to determine the implementation of public information transparency from a human rights perspective. The results of the study indicate progress in policies and legal umbrellas for the implementation of information transparency, but there are several significant obstacles, including lack of budget funds, lack of human resources, and lack of understanding of the right to access information among the community. Furthermore, to improve public information transparency, it is necessary to increase training and capacity for government officials, strengthen monitoring mechanisms, and provide more intensive education to the community. The main reasons include the development of a more transparent and accessible information system, and advocating for the right to information that plays a role in the fundamental components of human rights.